Stress localisation in lamellar cementite and ferrite during elastoplastic deformation of pearlitic steel studied using diffraction and modelling. (April 2020) - Gadalińska, E.; Baczmański, A.; Braham, C.; Gonzalez, G.; Sidhom, H.; Wroński, S.; Buslaps, T.; Wierzbanowski, K.
Abstract: Synchrotron X-ray diffraction was applied to study the evolution of lattice strain and stresses in both phases of pearlitic steel during a tensile test. The advantage of the methodology used in this work is the possibility of experimental study of stress localisation, which is directly determined from measurements and can be used to study the process of strain strengthening of lamellar pearlite. It was found that in the elastic range of deformation, both cementite and ferrite are loaded similarly due to the nearly equal elastic properties of both phases, while plastic deformation leads to significant load transfer from ferrite to cementite. Due to the complexity of the lamellar microstructure of the material, the classical elastic-plastic self-consistent model does not correctly predict the partitioning of the stresses between phases during plastic deformation. Therefore, the grain-matrix interaction given by the self-consistent model was modified and successfully applied to simulate the interaction between phases. The synchrotron experiment allowed us to determine the critical resolved shear stresses of ferrite phase in the pearlitic steel subjected to different thermal treatments. The role of cementite in material strengthening was evaluated on the basis of the evolution of von Mises stress, experimentally determined in both phases. It was found that during plastic deformations, the von Mises stress does not change significantly in ferrite compared to an important increase in elastically deformed cementite. Therefore, the partitioning of stresses between phases is mainly responsible for the strain strengthening of the tested pearlitic steel exhibiting fully lamellar microstructure. Highlights: Using synchrotron diffraction, stress tensor can be determined for different phases. Plastic deformation of pearlite depends on von Mises stress in the phases. High stress transferred to cementite leads to strengthening of pearlite. Second order stresses are generated in ferritic phase during plastic deformation. Experimental stress concentration tensor can be used to verify elastic-plastic model.